ESTABLISHING CHECKLISTS AND VALUATION MATRICES FOR TRANSPORTATION INVESTMENT PROJECTS - Altun, D. S.; Turgut, S. (SCIBULCOM LTD, 2016)
One of the factors driving the expansion of the road transport network is the need to meet the raw material requirements faster, to ship the goods to the market and to ensure the goods are delivered to the consumers, as a result of the industrial revolution which in turn gave rise to a rapid development era. The development and transformation processes during the 18th and 19th centuries triggered inter-industry relationships and brought about a socio-economic and cultural transformation along with a change which came with its own spatial consequences. A variety of ecological problems and risks increasingly emerging are one of the, if not the foremost, indirect consequences in terms the environment. It is intended to present the results of a study on establishing checklists and valuation matrices which give a better insight on the ecological effects of transportation investment projects. A method involving identification and analysis of the problem and determining the risk level based on the ERA (Ecological risk assessment) guidelines issued by USEPA (United Nations Environmental Protection Agency) in 1998 was employed in the study. The impact of transport investment projects on ecological structure, namely soil, water, climate, biotope and visual landscape will be highlighted with detailed breakdowns. The relationship matrix between environmental factors and the activities during the construction and operation phases of the projects will be examined from a natural and socio-economic-cultural standpoint and in the next step the anticipated occurrence of risks at relevant phases will be evaluated through the environmental impacts matrix.
Keywords: transportation projects; ecology; ecological risk assessment; RISKS; MANAGEMENT; SECURITY; ROADS; Chemistry